Differences in leaf pigments content and stomata distribution across eight Hevea species - Iffah Hazirah M.N.,; Suhaizan L.,; Shamsul Bahri A.R.,; Nurul Faziha I.,; Ong, Chin Wei (Penerbit Universiti Kebangsaan Malaysia, 2017)
Photosynthesis is very important to plants in order to produce their own food. The study of this process involves wide range of field including morphology, physiology, and biochemical studies. In this study the analysis of leaf pigments content including chlorophyll and anthocyanin content and stomata distribution that directly and indirectly involve in photosiynthesis were conducted. Eight Hevea species that are H. brasiliensis, H. camargoana, H. guinensis, H. benthamiana, H. rigidifolia, H. nitida, H. spruceana, and H. pauciflora were analyzed. Between these eight species, H. brasiliensis has the highest chlorophyll content while H. rigidifolia with the lowest chlorophyll content. Meanwhile, the anthocyanin content was found to be the highest in H. guinensis (36.747 mg/L) and lowest in H. camagoana (15.1 mg/L). Stomata distribution that directly involves in gas exchange during photosynthesis was found to be high in H. camargoana (190.55/mm2) and low in H. rigidifolia (92.25/mm2). As a conclusion, this study can be used as a guideline to indicate the physiological state and functional of the plant leaves as a result from analysis of chlorophyll and anthocyanin content and also the distribution of stomato.